PHYTOCHEMICAL STUDY OF CELL CULTURE JATROPHA CURCAS - ELFAHMI ELFAHMI; ARTRI; KOMAR RUSLAN (BIOTROPIA, 2011)
Jatropha curcas belongs to the Euphorbiaceae family which has potential economically. This plant has been reported to contain toxic compounds such as curcin and phorbol ester and its derivatives. These compounds may become a problem if J. curcas will be explored as a source of biofuel. In order to provide safety plants, the research on the study of phytochemical and initiation of cell and organ culture have been carried out. J curcas which has been collected from different regions in Indonesia showed to contain relatively the same profile of chemical contents. Dominant compounds that were detected by GCMS are hidrocarbon such asÂ  2-heptenal, decadienal, hexsadecane, pentadecane, cyclooctane etc, fatty acid such as oktadecanoate acid, etthyl linoleate, ethyl stearate, heksadecanoate acid and steroid such as stigmasterol, fucosterol, sitosterol. No phorbol ester and its derivatives have been detected yet by the GCMS method. Callus and suspension cultures of J. curcas have been established to be used for further investigation. Â  Keywords: Jatropha curcas, phytochemical, biofuel, cell culture, steroid, hydrocarbon, fatty acid